Wood pellets transport with vibrating conveyor: experimental for DEM simulations analysis - Daniel Gelnar (Nature Portfolio, 2021)
Abstract This work presents a comprehensive overview of the mechanical-physical parameters of the transport material affecting the vibratory transport. For this purpose, spruce pellets of different lengths, oak rods and spruce crush were tested. The determined parameters were particle size distribution and shape, internal friction, static and dynamic angle of repose. The samples were transported by a patented validation vibrating conveyor. Various settings were used. The results show that by changing the shape, it is possible to reduce friction or resistance as well as energy intensity during transport. It was observed that perfect shapes and lighter particles have lower friction, but a more pronounced bounce. Therefore, it does not form a typical pattern during transport, as in the case of an imperfectly shaped one. There is also included a simulation of the discrete element method. The study shows the possibility of the vibration machine where the material can be conveyed either directionally or sorted.